The loss of indirect interactions leads to cascading extinctions of carnivores. (28th February 2013) - Sanders, Dirk; Sutter, Louis; van, F. J. Frank; Eubanks, Micky
Abstract Species extinctions are biased towards higher trophic levels, and primary extinctions are often followed by unexpected secondary extinctions. Currently, predictions on the vulnerability of ecological communities to extinction cascades are based on models that focus on bottom‐up effects, which cannot capture the effects of extinctions at higher trophic levels. We show, in experimental insect communities, that harvesting of single carnivorous parasitoid species led to a significant increase in extinction rate of other parasitoid species, separated by four trophic links. Harvesting resulted in the release of prey from top‐down control, leading to increased interspecific competition at the herbivore trophic level. This resulted in increased extinction rates of non‐harvested parasitoid species when their host had become rare relative to other herbivores. The results demonstrate a mechanism for horizontal extinction cascades, and illustrate that altering the relationship between a predator and its prey can cause wide‐ranging ripple effects through ecosystems, including unexpected extinctions.